Squamous Cell Carcinoma Originating from Adult Laryngeal Papillomatosis: Case Report and Review of the Literature - Ribeiro El-Achkar, Vivian Narana [UNESP]; Duarte, Andressa; Saggioro, Fabiano Pinto; Verissimo De Mello Filho, Francisco; Leon, Jorge Esquiche; Ribeiro-Silva, Alfredo; Kaminagakura, Estela [UNESP] (Hindawi Ltd, 2018)
Background. The malignant transformation of laryngeal papillomatosis (LP) into squamous cell carcinoma (SCC) can occur in up to 4% of LP cases. The low-risk HPV types 6 and 11 are those that are most commonly related to LP; however, high-risk HPV types may be present. The present study reviews the literature on cases of malignant transformation of LP in adults and reports a clinical case. Case Report. A 47-year-old male patient exhibiting hoarseness for 4 months presented an exophytic lesion in the right palatine tonsil and a digitiform-like lesion in the right vocal fold. The biopsy revealed a well-differentiated SCC in the vocal cord, which showed a transition zone with a squamous papillomatous lesion. By using the chromogenic in situ hybridization (CISH) test, both lesions showed a positive result for high-risk HPV types 16 and 18 and negative for low-risk HPV types 6 and 11. The final diagnosis was SCC arising from LP. The patient underwent surgical treatment. After 36 months of follow-up, no signs of recurrence were observed. Results. The literature review revealed 25 cases of malignant transformation into SCC of LP with adult onset. Of these, only 9 cases were assessed by CISH and/or PCR for HPV identification, of which 7 were positive. The current study focuses on the eighth case, suggesting the involvement of the high-risk HPV types in its pathogenesis. Conclusions. LP is considered a benign lesion with the potential for malignant transformation, which reinforces the need for its early diagnosis and the constant monitoring of patients with LP.